Therapeutic effect of two muscle strengthening programs in patients with patellofemoral pain syndrome. A randomized controlled clinical trial - Luisa Fernanda Prieto-García; Edgar Cortés-Reyes; Gilberto Lara-Cotacio; Lizeth Catherine Rodríguez-Corredor (Revista de la Facultad de Medicina)
Introduction: Patellofemoral pain syndrome (PFPS) is one of the most common musculoskeletal disorders affecting the knee joint. Conservative treatment reduces pain and improves functional capacity in the short and medium-term.